Strategi Penguatan Identitas Produk UMKM lewat Desain Label: Studi Kasus di KUBE Sejahtera, Kelurahan Tanjung Uban Selatan, Kabupaten Bintan - Andrian Hanturri; Bail Ihsan; Dina Aulia; Era Dania; Jibril Pratama Artha Sandi; Nely Santika; Ramadhan Eka Putra; Sonia Nur Adilla; Tasia Tasia (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The community service activity through KKN 15 UMRAH in Tanjung Uban Selatan Village, Bintan Regency, aims to emphasize the product identity of the KUBE Sejahtera MSME through packaging label design. This MSME previously experienced marketing problems due to simple, unattractive product labels that did not meet BPOM standards, making it difficult for consumers to recognize and compete in the formal market. KUBE Sejahtera consists of ten members offering various types of food products such as banana chips, potato chips, onion cuttings, cookies, and peyek. A participatory approach was implemented so that KUBE members not only received results but also actively participated starting from identifying problems, discussing needs, to designing labels using a simple application. The results of the activity showed an increase in members' understanding of the importance of labels as a marketing strategy, as well as the birth of new label designs that are more attractive, professional, and in accordance with regulations. Various products successfully developed new visual identities with more prominent names and appearances, such as Ketas Potato Chips, MaYure Sejahtera Onion Cuttings, Kerpi'la, and Suka-Suka Peyek. This change has had a positive impact, marked by increased member confidence in selling products and broader opportunities to expand market reach. Overall, this program demonstrates that simple interventions through label design can increase the competitiveness of local products and serve as an effective strategy for empowering MSMEs. It is hoped that this success can be emulated by other business groups to support sustainable community economic growth.